P-476 Why are they not coming back? A single-center follow-up study on oncological women oocyte's storing for fertility preservation. (30th June 2022) - Immediata, V; Baggiani, A; Cirillo, F; Zanagnolo, M.F; Ronchetti, C; Morenghi, E; Specchia, C; Levi-Setti, P.E
Abstract: Study question: Which is the return rate and which factors are responsible for the non-return in cancer patients who underwent oocyte cryopreservation for fertility preservation? Summary answer: Return rate was 11.7%. Young age at freezing, lack of a partner and type of cancer were the main factors responsible for the non-return. What is known already: Improvements in oncological early diagnoses and therapies have significantly increased the survival rates of patients, allowing clinicians to focus on long-term quality-of-life issues, such as access to motherhood. An extensive literature on the importance of fertility preservation (FP) has been produced thanks to the growing number of patients undergoing FP cycles over the years. Nevertheless, the rates of patients returning to use their cryopreserved material have shown to be considerably low, ranging from 5 to 8%. Significant data regarding the reasons that might explain such low return rates are still scarce. Study design, size, duration: This is a single-center follow-up retrospective study that includes all women who underwent oocyte cryopreservation cycles for oncological purposes at referral University affiliated center, from January 2001 to December 2017. Participants/materials, setting, methods: The database consists of 171 patients, among those 110 (64%) were diagnosed with breast cancer, 45 (26%) hematological cancer, 5 (3%) gynecologic cancer and 11 (7%) other cancers. Data about returned patients were retrieved from internal registries. Non-returned patients were assessed by standardized phone survey on health and marital status, family projects, spontaneous conceptions, and reasons why they had not returned to use their gametes. A univariate analysis between returned and non-returned patients was performed. Main results and the role of chance: Among the 171 women who underwent oocyte cryopreservation, 9 (5%) died and 17 (10%) were lost at follow up. In the remaining 145-patient group, the mean age at freezing was 32.2±6.1 and at follow-up 38.2±6.7 years. A total of 20 patients (11.7%) returned to use their frozen material and 125 did not. In the non-returned group, 37 (29.6%) did not have a partner, 10 (8%) had a previous spontaneous conception and 15 (12%) had recurrent malignancy at the time of follow-up. In the univariate analysis, younger age at freezing (31.8±6.2 vs 35.2±4.7; p 0.018), lack of a partner (p 0.002), type of cancer (other than breast cancer; p 0.024) were the significant factors in the non-returned group. As for the personal reason for not coming back, patients mainly answered as follows: lack of a partner (29, 23.2%), desire of spontaneous motherhood (24, 19.2%), previous spontaneous pregnancies after FP procedures (16, 12.8%), and still ongoing hormonal therapy for breast cancer (13, 10.4%). Nonetheless all of them confirmed their will to keep the storage of their oocytes. Limitations, reasons for caution: The study population consists of a limited number of patients from a single Italian Fertility Center. Since the Italian law limits ART access to heterosexual couples, this setting may limit any possible adaptation of the study to other countries, with different legislations. Wider implications of the findings: The impact of a cancer diagnosis on a woman's maternal desire, sentimental status and life priorities should be studied more thoroughly. Moreover, it is important to encourage studies investigating so long hormonal therapy suppression in breast cancer patients seeking pregnancy in order to reduce their time to pregnancy. Trial registration number: na